2016
DOI: 10.1590/1981-5344/2407
|View full text |Cite
|
Sign up to set email alerts
|

Influência do ambiente físico de trabalho na criação do conhecimento nas organizações

Abstract: RESUMO O ambiente de trabalho pode contribuir para o desempenho e produtividade dos trabalhadores bem como para a troca de informações entre colegas de trabalho que, ao interagirem, promovem a criação de conhecimento. O objetivo do presente estudo foi o de identificar a influência da satisfação com os aspectos tangíveis do ambiente construído sobre os aspectos intangíveis do processo de criação do conhecimento em empresas do Rio Grande do Sul. O método adotado foi de natureza quantitativa com abordagem descrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
1
4
0
5
Order By: Relevance
“…The management of PST combined with COD practices can enhance knowledge retention processes in the organization, increasing the bases of know-how and know-why, and converging so that operational processes enable organizations to adequately respond to the environmental challenges they encounter. It was also observed that MST is related to the COD dimension of the OL construct, both at the bank and at the CSOPI, confirming studies by Graciola et al (2016) and Cacciatori et al (2011). COD of IL of competencies is also predicted by the PST promoted by the two organizations, confirming the findings of King (2009), Alvarenga and Vieira (2011), Catino and Patriotta (2013), Popadiuk and Ayres (2016).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The management of PST combined with COD practices can enhance knowledge retention processes in the organization, increasing the bases of know-how and know-why, and converging so that operational processes enable organizations to adequately respond to the environmental challenges they encounter. It was also observed that MST is related to the COD dimension of the OL construct, both at the bank and at the CSOPI, confirming studies by Graciola et al (2016) and Cacciatori et al (2011). COD of IL of competencies is also predicted by the PST promoted by the two organizations, confirming the findings of King (2009), Alvarenga and Vieira (2011), Catino and Patriotta (2013), Popadiuk and Ayres (2016).…”
Section: Discussionsupporting
confidence: 85%
“…Positive and significant relationships between MST and COD are reported in various studies. The research by Graciola et al, (2016), conducted with industry and service providers in the state of Rio Grande do Sul (Brazil), finds that the perception of physical space, furniture, and equipment is positively related to the logging and communication of knowledge in documents and technological elements of information systems, while Cacciatori, Tamoschus, and Grabher (2012) find a significant relationship between the support of an integrative system and COD in creative industries in various European Union countries. Therefore, H2 develops into:…”
Section: Organizational Support For Transfer Of Learning (Ost)mentioning
confidence: 99%
See 1 more Smart Citation
“…The improvement of the satisfaction with the built environment quickly provides meetings between people, promoting information sharing periods (Graciola et al, 2016). The location of the working site has a high impact on psychological user satisfaction related to social contact.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Organizacional" quando correta cria um ambiente propício para o compartilhamento de conhecimento entre os colaboradores dentro e fora da organização(SILVA, 2004;POPADIUK;SANTOS, 2010;GRACIOLA et al (2016).Cruz e Nagano (2008) destacam a necessidade de valoração do ambiente de conhecimento organizacional, principalmente a espontaneidade dos indivíduos para compartilhar o conhecimento. Para Cunha, Yokomizo e Capellini (2011) um ambiente solícito é essencial para haver a troca de informações e conhecimentos dentro de uma organização.…”
unclassified